(untitled) (Laisvalaikio tyrimai, 2023)
During the Covid-19 pandemic, the simplest economic, economic and social activities were restricted in many countries. The introduction of pandemic restrictions particularly affected sports organisations: it was forbidden to provide sports services, organise mass sports events, and restrictions were applied on group training and any social gatherings. Various organisational, technological, marketing, communication, public relations and other innovations allowed sports organisations to discover new operational opportunities, generate cash flows, and maintain the continuity of sports organisations’ activities in crisis conditions. The success of innovation is determined by certain factors, named as innovation implementation planning, strategic leadership, etc. Therefore, it is relevant to study what factors determine the success of a sports organisation implementing crisis innovations. The purpose of the study is to determine the factors determining the success of the implementation of crisis-driven innovations in sports organisations. Work tasks: • To examine the theoretical aspects of implementing crisis-driven innovations in sports organisations; 2. To determine what crisis-driven innovations are implemented in the studied sports organisations; 3. To determine what factors led to the success of the implementation of crisis-driven innovations in the studied sports organisations. Research methods: analysis of scientific literature; structured interview; content analysis. Main results. The research results show that during the pandemic, the studied basketball clubs implemented the following crisis-driven innovations: 1. Necessary innovations according to legislation (disinfection innovations, separation of zones, temperature measurement technologies); 2. Marketing innovations (advertising innovations, innovations in the development of social network marketing, e-commerce, including the sale of licensed products); 3. Innovations in remote communication with fans (innovation of match previews on online platforms, "cardboard image" innovation, development of social networks, fans inclusion in the commercialisation of social media, creation of a virtual community of fans, e-sports); 4. Innovations to support the internal work of the club (remote communication within the club using Teams software, online training of basketball players). The most successful crisis-driven innovations were communication within the club and in the office through Teams; content marketing in social networks and its commercialisation, as well as solutions for selling advertising content during pandemics. Conclusion of the work: The success of the implementation of crisis-driven innovations of the basketball clubs studied during the pandemic was determined by the entrepreneurial spirit of the organisation, know-how in the field of innovation, strategic and tactical, quick planning, effective teamwork and having specialists in the organisation, managerial and innovative competence of managers, charismatic and innovative leadership, work with personnel (strengthening microclimate, encouraging the cooperation, psychological support for employees, motivation, openness in communication with employees), sufficient financial and human resources. Keywords: crisis innovation; implementation of innovations; success factors.